Impact Of ISO 9001: 2008 Certification On Consumer Satisfaction - Husseini, Saleh Ali; Al-Shami, Samer Ali Hussein; Fam, Soo Fen; Al derei, Saif (Institute Of Advanced Scientific Research, 2018)
The objective of this study aims to describe and examine the effect of the organizations obtaining the certificate of conformity with ISO 9001: 2008 on the satisfaction of their consumers among industrial companies in Damascus Governorate. A survey was distributed to 340 consumers, while One-Sample Statistics was used to measure the level of customers’ satisfaction in four large enterprises. The results showed that the obtaining ISO 9001: 2008 certification has positive effect on consumer satisfaction proxied by (consumer complaints, frequent buying, positive buying trends, quality perceived by consumers and quality provided by companies.